Ferrocenium Ion Confinement in Polyelectrolyte for Electrochemical Nitric Oxide Sensor. Issue 13 (4th April 2019) - Mathi, Selvam; Gupta, Prashant Kumar; Kumar, Rudra; Nagarale, Rajaram K.; Sharma, Ashutosh
Abstract: Manuscript reports on ferrocenium ion entangled in polyelectrolyte matrix as a redox platform for oxidative and reductive sensing of nitric oxide (NO). It was prepared by oxidation of ferrocene in diethyl ether followed by extraction with polystyrene sulfonic acid (PSS) and Nafion® solution. The presence of stable ferrocenium cation was confirmed by FT‐IR, UV‐visible spectra, 1 HNMR and XRD. It results into a stable cyclic voltammogram in 100 mM Phosphate buffer, pH 7 solution with Ag/AgCl reference and Pt wire counter electrodes. The electrode sensitivity towards NO was confirmed through the increase in oxidative current at +750 mV and reductive current at −800 mV by the addition of 100 μL saturated NO solution. The chronoamperometric response for NO oxidation followed linearity in the concentration range of 200 nM to 3.5 μM. The lower detection limit and sensitivity were found to be 200 nM and be 33.29 μA/μM/cm 2 respectively. The reductive response also followed a linear trend in the concentration range of 100 μM to 1.2 mM with 15.15 μA/μM/cm 2 sensitivity and 100 μM detection limit. It indicates ferrocenium ion entanglement within polyelectrolyte matrix and its viability as a redox platform for oxidative as well as reductive sensing of nitric oxide. Abstract : The manuscript reports on ferrocenium ion entangled in polyelectrolyte matrix as a redox platform for oxidative and reductive sensing of nitric oxide (NO). The chronoamperometric response for NO oxidation followed linearity in the concentration range of 200 nM to 3.5 μM indicating a potential platform for electrochemical sensing of nitric oxide. The graphical abstract shows the chronopotentiometric response and snap shot of solution containing Nafion‐FC and neat FC after passing nitric oxide gas for a different time.